THE SUI GENERIS OF NUCLEAR FATWA UNDER CUSTOMARY INTERNATIONAL LA - Jaber Seyvanizad (BRICS Law Journal)
Due to the fluctuating nature of the Customary International Law, emerging customs have had good potential to appear in several forms during the past decade. In other words, there are various legal mechanisms indicating the genesis of CIL. One of these forms is the internationally known unilateral act of State which can be potentially recognized as a customary rule. The best example of a unilateral act of State would be Truman Proclamation which was transformed into a customary international rule concerning law of seas. With regards to the same legal framework and acts like Truman Proclamation, this research tries to answer the question that how the sui generis of fatwa in a custom-construction process concerning international law of WMD and through the modernized methodology can contribute. Illustrating the superiority of fatwa over the sui generis treaties on one hand and restricting mechanisms like NPT on the other, it can be indicated that the first steps concerning the genesis of a new customary approach in the field of international law of WMD has been derived from nuclear fatwa.